Comunicação verbal e não-verbal: um olhar sobre as expressões faciais de emoção em tradutores intérpretes de língua de sinais-português - Guilherme, Rafael Silva (2023)
Facial expressions of emotion (FEE) such as joy, sadness, anger, disgust, fear, surprise, and the neutral face (Ekman & Friesen, 1976) can be characterized as part of nonverbal communication. They are spontaneous, universal, non-symbolic expressions produced and recognized by individuals who communicate through both oral and sign languages (LS). These expressions form part of the grammar of LS and are considered Non-Manual Markers. The Sign Language and Portuguese Interpreter - TILSP is the professional who communicates through LS. In their formal training, TILSPs learn specific language competencies and skills, and learning and training in facial expressions are necessary for their development in the interpretation and translation process. The overall objective of this thesis was to investigate the influence of learning and experience with sign language on the recognition and display of facial expressions of emotion by sign language interpreters. Four independent studies were proposed. The first article conducted a scoping review of studies on FEE and LS. The results indicate that most studies were conducted with deaf signers compared to individuals without knowledge of sign language, and no significant differences were found between the groups. The second article investigated whether learning sign language could influence the recognition of FEE in TILSPs using digital avatar images with human faces. The results suggest that professionals did not show better accuracy in recognizing FEE. However, as expected, images with male faces and higher intensity were statistically more recognized than those with lower intensity and female faces. In the third article, the same method used in the previous study was replicated, but static (photographs) and dynamic (videos) images were added. This study investigated whether learning sign language could influence the recognition of FEE. The results suggest that professionals performed better in various facial recognition tasks, being faster and reporting fewer difficulties. Regarding stimuli, images with the avatar's face were more recognized than others. The fourth study aimed to investigate the influence of learning or experience in Brazilian Sign Language (Libras) on the production of FEE in sign language interpreters. The results indicate that, overall, learning sign language did not have a significant impact on the production of emotions. The studies presented allow us to understand that learning sign language can indeed influence the recognition of FEE in hearing individuals studying or working in sign language translation and interpretation. However, this recognition may not occur for all emotions. On the other hand, in relation to the production of FEE, our findings do not support the same influence. The results of this thesis can contribute to the training of TILSPs, including studies on FEE, and encourage future research in the field, expanding discussions on emotional expressions in sign language communication.